Life cycle toxicity assessment of earthworms exposed to cadmium-contaminated soils - Chen, Wei-Yu (Ecotoxicology (London, England), 2017)
Cadmium (Cd) is of great concern in the soil environment and it can damage terrestrial organisms. The purpose of this study was to employ a toxicokinetic/toxicodynamic (TK/TD) approach to investigate the effects of toxicologically relevant Cd accumulation on the life cycle growth of earthworms (Lumbricus rubellus and Eisenia fetida) and to assess potential terrestrial ecosystem risk. We reanalyzed growth toxicity and whole body and pellet accumulation data linked with TK/TD and life cycle growth models to estimate key rate constants. The growth risk of earthworms exposed to Cd was also assessed. This study found that the estimated whole body killing rate constant (0.114 g d μg-1) was much lower than that of pellet (0.248 g d μg-1). The recovery rate constant for whole body (6.02 d-1) was much higher than that of pellet (2.91 d-1). We also employed a life cycle-based probabilistic risk assessment model to estimate the growth inhibition risk for earthworms in response to environmentally relevant concentrations of Cd in Taiwan. Results showed that earthworms had a 90% growth inhibition probability risk of body weight, which was lower than 872.33 mg based on assessment of toxicologically relevant Cd accumulation. This study suggests that toxicologically relevant Cd accumulation could accurately reflect the capacity of Cd toxicity to earthworms. The integrated life cycle toxicity of earthworms exposed to Cd in this study provides a robust and applicable tool for the management of ecological risk assessment of Cd-contaminated soil